2021
DOI: 10.3389/fcell.2021.580834
|View full text |Cite
|
Sign up to set email alerts
|

Construction of circRNA-miRNA-mRNA Network for Exploring Underlying Mechanisms of Lubrication Disorder

Abstract: Lubrication disorder is a common health issue that manifests as insufficient sexual arousal at the beginning of sex. It often causes physical and psychological distress. However, there are few studies on lubrication disorder, and the complexity of circular RNA (circRNA) and the related competing endogenous RNA (ceRNA) network in lubrication disorder is still poorly known. Therefore, this study aims to build a regulatory circRNA-micro (mi)RNA-mRNA network and explore potential molecular markers of lubrication d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…According to a new bioinformatics study of acute MI, circUBXN7 protects cardiomyocytes from apoptosis and inflammation following H/R injury via regulating miR-622 and maintaining MCL1 expression [ 28 ]. The purpose of this study was to see if the function of miR-143-3p/NPY-mediated calcium influx response in cardiac microvascular I/R damage was a downstream mechanism of mmu_circ_0000021 [ 29 ]. Next, inhibiting mmu circ 0000021 reduces cardiac microvascular I/R damage and increases microvascular perfusion, hence enhancing microvascular integrity and reducing microvascular hyperpermeability, which promotes cardiomyocyte death and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…According to a new bioinformatics study of acute MI, circUBXN7 protects cardiomyocytes from apoptosis and inflammation following H/R injury via regulating miR-622 and maintaining MCL1 expression [ 28 ]. The purpose of this study was to see if the function of miR-143-3p/NPY-mediated calcium influx response in cardiac microvascular I/R damage was a downstream mechanism of mmu_circ_0000021 [ 29 ]. Next, inhibiting mmu circ 0000021 reduces cardiac microvascular I/R damage and increases microvascular perfusion, hence enhancing microvascular integrity and reducing microvascular hyperpermeability, which promotes cardiomyocyte death and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that some lncRNAs are closely related to lesions of nerves ( Zhao et al, 2013 ), blood vessels ( Simion, Haemmig & Feinberg, 2019 ), vaginal smooth muscles, and vaginal epithelium ( Wei et al, 2020 ). In previous research, next-generation sequencing was conducted to mine differentially expressed circRNAs in the vaginal epithelial tissue of women with vaginal LD, and circRNA-miRNA-mRNA networks were conducted ( Camilleri, Sandler & Peery, 2020 ; Cong et al, 2021 ; Zhang et al, 2019 ). Few studies have explored the relationships between lncRNA and vaginal LD.…”
Section: Discussionmentioning
confidence: 99%
“…Our group identified miR-137 and its downstream effector AQP2 as important molecules involved in the regulation of vaginal lubrication ( Zhang et al, 2018 ). Additionally, we also previously explored the differentially expressed circRNAs in women with vaginal LD, constructed a circRNA-miRNA-mRNA network, and found that hsa-miR-212-5p and hsa-miR-874-3p were associated with LD development ( Cong et al, 2021 ; Zhang et al, 2019 ). These results provided some molecular basis and clues for understanding the development of vaginal LD.…”
Section: Introductionmentioning
confidence: 99%